Cobalt complexes containing salen-type pyridoxal ligand and DMSO for cycloaddition of carbon dioxide to propylene oxide. (1st March 2020) - Hwang, Saem; Ryu, Ji Yeon; Jung, Sung Hoo; Park, Hyoung-Ryun; Lee, Junseong
Graphical abstract: Two new cobalt complexes possessing salen-type pyridoxal ligands were prepared and used in catalytic reaction of cycloaddition of CO2 to propylene oxide, providing considerable activities. Abstract: Cobalt complexes containing a salen-type pyridoxal ligand with pyridine were synthesized as a new Co(III) catalytic system for the cycloaddition of carbon dioxide. Two cobalt(III) complexes possessing a salen-type pyridoxyl ligand were synthesized by the reaction of pyridoxal ligands (pyr2 en = ( N, N′ -bis(pyridoxylideneiminato)ethylene) and pyr2 cy = ( N, N′ -bis(pyridoxylideneiminato)cyclohexane)) and Co(OAc)2 and characterized by various analytical methods, including infrared spectroscopy and high-resolution mass analysis. Single-crystal X-ray crystallography analysis confirmed that the cobalt pyr2 en complex had a distorted octahedral structure: the tetradentate Schiff base ligand binds the cobalt metal in one plane, and the metal center adopts an octahedral geometry by the additional coordination of acetate and dimethyl sulfoxide. The synthesized complexes were used as catalysts in the cycloaddition of carbon dioxide (CO2 ) to propylene oxide. The catalysts showed high activity for cycloaddition between CO2 and epoxides, even at a low loading (0.5 mol%), in the presence of various cocatalysts.